DETERMINAN KEPUASAN PEDAGANG SEBAGAI NASABAH BRI - Agung, Inayah Ayu (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
This study analyzes the factors that affect customer satisfaction. Customers will be satisfied if the bank is able to deliver the quality expected. The quality of service, price, product, promotion and the location is an important factor supporting the performance of BRI for the better. The purpose of this study was to analyze the influence of service, price, product, promotion, and location to the satisfaction of merchants who are customers of BRI Branch Unit Kemlagi Mojokerto. The independent variables consist of service, price, product, promotion, and location. The dependent variable is satisfaction. Using multiple regression analysis. Samples taken as many as 28 customers using quota sampling. Data collection techniques by distributing a questionnaire using Likert scale. The results showed that simultaneous service, price, product, promotion, and location of positive and significant impact on satisfaction. Partially service, price, product, promotion, and location of positive and significant impact on satisfaction. Variable service, price, product, promotion and location can be a determinant of customer satisfaction BRI.